2014
DOI: 10.3892/ijo.2014.2561
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-proteasomal degradation of antiapoptotic survivin facilitates induction of apoptosis in prostate cancer cells by pristimerin

Abstract: Pristimerin (PM), a quinonemethide triterpenoid, is a promising anticancer agent with potent antiproliferative and apoptosis-inducing activities against cancer cell lines. However, the anticancer activity and mechanisms of PM in prostate cancer cells have not been adequately investigated. Here we report that the degradation of survivin plays an important role in the antiproliferative and proapoptotic effects of PM in carcinoma of the prostate (CaP) cell lines. Treatment with PM inhibited proliferation and indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…In addition, it has been reported that pristimerin has promising clinical potential as both a therapeutic and chemopreventive agent for various types of cancer such as pancreatic cancer, glioma, leukemia, cervical cancer, prostate cancer and breast cancer (6)(7)(8)(9)(10)(11). Pristimerin has been shown to induce cell death via a number of several mechanisms, including proteosome inhibition, caspase activation, inhibition of cell cycle progression, and suppression of antiapoptotic nuclear factor kappa B (NF-κB) and Akt signaling pathways (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that pristimerin has promising clinical potential as both a therapeutic and chemopreventive agent for various types of cancer such as pancreatic cancer, glioma, leukemia, cervical cancer, prostate cancer and breast cancer (6)(7)(8)(9)(10)(11). Pristimerin has been shown to induce cell death via a number of several mechanisms, including proteosome inhibition, caspase activation, inhibition of cell cycle progression, and suppression of antiapoptotic nuclear factor kappa B (NF-κB) and Akt signaling pathways (6,9).…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferative activity of pristimerin goes beyond colon-related cancers, it is extended to breast [346][347][348][349][350], melanomas [351], osteosarcoma [352], pancreatic [353,354], and prostate cancers [355][356][357][358]. Herein, we describe a few examples focusing on articles that have demonstrated potential mechanisms of action.…”
Section: Pristimerinmentioning
confidence: 99%
“…Its progression was reported to be prevented by pristimerin-induced inhibition on HIF-1α and SPHK-1, which stimulates different cellular processes including cell proliferation, cell survival, and angiogenesis [355,369]. Pristimerin also induced apoptosis of prostate cancer cells through activation of mitochondrial apoptotic pathway [358], ubiquitin-proteasomal degradation [357], and inhibition of proteasomal chymotrypsin-like activity (a complex associated with cell proliferation, apoptosis, and cancer progression) [370,371]. These summarized findings provide evidences regarding pristimerin antiproliferative and cytotoxic activity as well as clinical benefits for treatment of different types of cancer.…”
Section: Pristimerinmentioning
confidence: 99%
“…* P<0.05, ** P<0.01, one-way ANOVA was used for statistical analysis. and the anti-apoptotic role of survivin in pristimerin-inducing apoptosis in prostate cancer cells (38), we hypothesized that survivin might be critical in pristimerin-inducing apoptosis in UM cells. The Omm 1 cell ectopic overexpression of survivin by lentiviral construct encoding survivin were more resistant to pristimerin than cells transfected with empty vector (Fig.…”
Section: Survivin Plays An Important Role In Pristimerin-induced Apopmentioning
confidence: 99%